PERAN ORANG TUA DAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR ANAK BERKEBUTUHAN KHUSUS USIA SD/MI - Rabiatul Adawiah; Yuliani; Adinda Zaryanisa; Afriliana Renti Mareta; Gita Putri Ardini; Ray Wanda Sahara; Surawan Surawan (STKIP Subang, 2026)
This study aims to examine the role of parents and peers in influencing the learning motivation of children with special needs at the elementary school level within an inclusive education context. Using a library research method with data analysis based on the Miles and Huberman model, the findings indicate that parents play a crucial role through emotional support and active involvement in learning, while peers contribute to enhancing students’ confidence and motivation through social interaction. These findings highlight the importance of synergy between parents and peers in creating an inclusive and supportive learning environment.